Assessing the Willingness to Accept Assisted Migration for a Sky Island Lizard - Zorondo-Rodriguez, F (Routledge, 2025)
Analyzing the social dimensions of species conservation measures is crucial. For species inhabiting sky islands (high–altitude landscapes), given the pressures of global change, one possible measure to implement is assisted migration. We evaluated the social willingness to accept an assisted migration of Black–green lizard, and determined which sociodemographic variables influenced the acceptance of this measure. This exercise was conducted in Las Cabras, a human settlement surrounding the mountains that could potentially receive assisted migration of the species. We corroborated our hypothesis that there was a willingness to accept assisted migration on public lands and not on private lands, but not regarding the willingness to assist on owned lands. We determined that aesthetic perception was an explanatory variable for willingness to accept assisted migration of Black–green lizard. We suggest that studies like ours can promote the national–level implementation of assisted migrations, contributing to the ongoing global discussion. © 2025 Taylor & Francis Group, LLC.